Ozonización De Residuos Líquidos Textiles Para Remoción De Sólidos Suspendidos Totales, Demandas Química Y Bioquímica De Oxígeno, Grasas Y Aceites - Pérez, Agustín Leiva; Andrade, Edison Macías; Farías, Teódulo Zambrano; Zambrano, Roy Barre; Párraga, Ricardo Montesdeoca; Candell, Joffre Andrade (European Scientific Journal, ESJ, 2018)
The study of the textile industry liquid wastes oxidation by ozone application in completed mixed batch reactors, with reaction times between 10 and 60 minutes, was developed according to previous observation tests. A SEFILTRA Ozone Generator, manufactured in Madrid, Spain, characterized by an air flow of 2 dm3/min), ozone concentration of 9,50 mg/dm3 , an O3production of 19 mg/min and %weight of 0,8. The contamination indicating parameters as Color, Turbidity, Total Suspended Solids, Chemical Oxygen Demand, Biochemical Oxygen Demand and, Fats and oils, showed satisfactory oxidative levels, with BOD5 and Fats and oils being the most oxidized within 50 minutes of reaction time. All contamination indicators were oxidized by ozone, according to second degree polynomial behavior, with correlation coefficients above 0,98.